Pengembangan Sistem Informasi Penjualan Di Toko Karunia Dengan Framework Spring MVC - Vincent Junaidi, Yohanes; Dewayani, Ery (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The aim of this research is to create a sales information system for Toko Karunia, which is a general store, by utilizing the Spring MVC framework. The research applied an agile approach with a scrum methodology for software development, using JavaScript as the programming language. The system development consists of features such as inventory management, sales tracking, customer management, and reporting. The implementation of this system provides a significant improvement in the store's operational efficiency and accuracy in sales processes. The outcome of this study can be beneficial for retail businesses with similar needs to enhance their sales processes using modern software technology.